Sustaining Rasicm in Popular Literature the Girl with Louding Her Voice by Abi Dare’ - Alfadlilah, Muna (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2024)
Popular fiction is part of popular literature that is very like and read by the society. The desire of the public to consume literary works is very related to tastes and what is viral in society at that time. Every that moves the public in the consumption of society is certainly driven by a belief, one of which is the belief in the issues that exist in society. One of the issues that exist in society is racism. Strong racism arises because of differences according to ideology in the western view. This study examines the analysis of sustaining racism with a postmodern approach in the novel The Girl with Louding Voice by Abi Dare'. Explaining that women cannot live freely and are not given the opportunity to run and continue their education. This article used postmodern approach with seeing the phenomenon about society to literature. The result of this study is that society still has several points of view regarding racism so that many consume this literary work. Fiction that is still hotly discussed by the public about the lives of black people. Keywords: Rasicm, postmodern, popular literature.